Fish assemblages in the trawling grounds of Northeastern Mediterranean: Comparison between the 1980s and 2020s - KURT, MERVE; GÜCÜ, ALI CEMAL (Mediterranean Marine Science, 2025)
Since the opening of the Suez Canal, the Eastern Mediterranean has been continuously affected by the influx of non-indigenous species (NIS), leading to significant changes in species composition. In this study, we focus on the temporal changes in marine teleost fish communities within one of the most heavily invaded shelf ecosystems. To examine changes in species assemblages, we integrated historical seasonal trawl data from the 1980s with recent data collected in 2022 along the Northeastern Mediterranean coast at depths of 0–25 m, 25–50 m, and 50–100 m. As a result, we identified 130 fish species, consisting of 37 NIS and 93 native species. Cluster analysis and Non-metric Multidimensional Scaling (NMDS) results revealed three main groups: a shallow water group, a deeper water group, and a western group, along with additional groups exhibiting sporadic occurrences. The western group, influenced by the presence of Posidonia oceanica meadows, has consistently been dominated by native biomass. However, the ratio of NIS to the total number of species has notably increased since the 1980s. The shallow water group, considered Por’s “Lessepsian Province”, is predominantly composed of NIS biomass and spans a depth range of 7 to 60 meters. In contrast, the deeper water group, which extends up to 82 meters, has maintained a relatively stable community dominated by native biomass over the years. However, since the 1980s, there has been a recorded increase in the contribution of NIS biomass and the overall proportion of NIS in the total species count within this group. Significant differences in community structure were correlated with depth and the spatially defined subregions within the study area. This study elucidates the dynamic nature of species assemblages in the continental shelf of the Northeastern Mediterranean and emphasizes the need for continuous monitoring to understand the ongoing transformations in these heavily impacted regions.